Madrasah development model based on strengthening the integrity values in Banyumas, Indonesia - Sutrimo Purnomo; Windhariyati Dyah Kusumawanti; Fatkhan Munif (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
This study aims to find an integrity-value-based madrasah development model in Banyumas, Indonesia. Madrasahs, as one of the Islamic educational institutions in Indonesia, play a strategic role in achieving national education goals. Therefore, they need to be developed optimally, and strengthening the values of integrity is a key solution for madrasah development. This qualitative field research employs a case study approach. Data collection techniques used include interviews, observation, and documentation. The results show that the integrity values developed by the madrasahs in Banyumas include hard work, responsibility, discipline, and cooperation, involving all members of the madrasah community, including the head of the madrasah, teachers, and students. The implementation of the madrasah development model through integrity values involves creating clear rules, managing and socializing these rules, and finally, habituating the madrasah community to follow them. By implementing these aspects, the madrasahs in Banyumas can strengthen their integrity values and, consequently, develop their institutions effectively.